Efficacy and safety of a carbon-dioxide ablative fractional resurfacing device for treatment of atrophic acne scars in Asians - Woraphong Manuskiatti (2018)
Background: Treatment of atrophic scars with a fractional laser resurfacing technique has demonstrated favorable outcomes, although data on the efficacy and adverse effects of this procedure in persons with dark-skinned phototypes are limited. Objective: This study was conducted to evaluate the efficacy and safety of carbon-dioxide ablative fractional resurfacing on atrophic acne scars in Asian individuals. Methods: Thirteen subjects (8 female and 5 male, aged 25-52 years) with skin phototype IV and atrophic acne scars were treated with 3 sessions of carbon-dioxide ablative fractional resurfacing laser on an average of 7-week interval. Objective (ultraviolet A-light video camera) and subjective (clinical evaluation by two blinded dermatologists) assessments were obtained at baseline and at 1, 3, and 6 months after the final treatment. Results: At the 6-month follow-up, 85% of the subjects were rated as having at least 25% to 50% improvement of scars. Improvement significantly progressed from the 1-month follow-up to the 6-month follow-up (P = .002). At 1 month after 3 treatments, surface smoothness (P = .03) and scar volume (P < .001) significantly improved, compared with baseline measurements. Of the subjects, 62% rated themselves as having at least 50% improvement in their scars. Mild postinflammatory hyperpigmentation was the most common adverse effect observed in 92% of the subjects or 51% of treatment sessions, and was completely resolved in an average of 5 weeks. Limitation: The small sample size was a study limitation. Conclusions: Carbon-dioxide ablative fractional resurfacing appears to be effective and well tolerated for the treatment of atrophic acne scars in Asians. © 2009 by the American Academy of Dermatology, Inc.